Pelatihan Pengolahan Data Penelitian Pendidikan IPA Menggunakan STATA Data Analysis - Sudirman Sudirman (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
The community service aims to increase the capacity of Universitas Qamarul Huda Badaruddin (UNIQHBA) lecturers in processing and analyzing science education research data using STATA Software. The method of community service was used for interactive training for two weeks with the Zoom application for 37 lecturers from UNIQHBA. To determine the participants' ability to use the STATA software, practice processing and data analysis were carried out using a science education case study guide provided by the facilitator. The evaluation was carried out at the end of the training to get participants' responses through online questionnaires that were then analyzed descriptively. The results of this community service were that as many as 89.32% of the participants were able to complete the practice correctly based on the assignments given, 89.74% of the presentations given by the facilitator were clear and easy to understand and will use STATA for the processing and analysis of their research data because it was easy to use. Most of the participants recommended further training using the STATA Software.